Relationship between attachment styles and personal resilience among Malaysian young adults - Muyang, Rebecca Eva; Mohd Jamil, Aifaa; Chan, Siaw Leng (Human Resource Management Academic Research Society, 2023)
The increasing prevalence of suicide attempts and cases among Malaysian young adults, particularly those aged 18 to 40, necessitates urgent research and intervention strategies. This study aimed to investigate the relationship between attachment styles and personal resilience among young adults in Malaysia engaged in romantic relationships. This cross-sectional survey research recruited 124 participants aged 18 to 40 involved in romantic relationships. The Relationships Questionnaire (RQ), the Resilience Scale (RS), and sociodemographic information were utilized to assess attachment styles and personal resilience. The findings of this study revealed a significant correlation between secure attachment style and personal resilience among Malaysian young adults in romantic relationships. The secure attachment style emerged as the prevailing one within this population, compared to the preoccupied attachment style. The finding also indicated that the overall level of resilience among young adults in Malaysia ranges from moderately low to moderate. Future research should explore additional factors influencing resilience, such as social support and cultural influences. Longitudinal studies can identify critical intervention points and developmental trajectories of attachment styles and resilience. This study also discusses the implication and contribution of the current study.